The storied church : a strategy for congregational renewal - Gorkos, Matthew (Fortress Press, 2021)
The Storied Church focuses on story-centered church renewal and is born of a suspicion that the restorative, transformative, life-giving function that stories have for us as individuals may serve communities of faithful people as well. If stories help us survive as human creatures, why can't they help churches survive? This book is a tool to empower pastors and lay leaders to effect revitalizing change in their faith communities. Each chapter includes questions for reflection.